2013
DOI: 10.1127/0003-5548/2012/0235
|View full text |Cite
|
Sign up to set email alerts
|

Primary tooth emergence in Polish children: timing, sequence and the relation between morphological and dental maturity in males and females

Abstract: The purpose of the present study was an assessment of differences between boys and girls in the process of emergence of primary teeth. This paper also provides updated data on the timing and sequence of primary tooth emergence in Polish children. The research were conducted in the years 2004-2008, and covered 865 children (437 boys and 428 girls) aged 3 to 36 months from all nursery and randomly selected "Healthy Child Clinics" in Lodz (central Poland). The first and last primary tooth emerged, on average: in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
3
7
1
Order By: Relevance
“…The GUSTO study in Singapore 24 did not find a sex-related difference; however, in the present study, we found a sex difference in the ETFPT, which was earlier in males. Our results align with previous studies that found that the primary teeth erupt earlier in males than in females 37–40 . The reason for the differences in the timing of tooth eruption between males and females is poorly understood.…”
Section: Discussionsupporting
confidence: 93%
“…The GUSTO study in Singapore 24 did not find a sex-related difference; however, in the present study, we found a sex difference in the ETFPT, which was earlier in males. Our results align with previous studies that found that the primary teeth erupt earlier in males than in females 37–40 . The reason for the differences in the timing of tooth eruption between males and females is poorly understood.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, no relationship was observed between gender and timing of the first deciduous tooth eruption, in agreement with the results of Neto et al, 22 Blewicz et al, 12 indicated that girls, whereas, Zadzinska et al, 13 Chio et al, 14 and Oziegbo et al, 15 reported that the eruption of the first deciduous tooth was earlier in boys; differences between their findings may result from ethnic differences among the studied populations. According to the results of the current study, there was no relationship between the type of feeding and timing of eruption of the first deciduous tooth, which was similar to the findings of Folayan et al, 23 while according to Martin-Moreno et al, 10 breastfeeding can change the pattern of the first deciduous tooth eruption.…”
Section: [ E P U B a H E A D O F P R I N T ]supporting
confidence: 91%
“…But a few studies have indicated that the mother's level of education can affect her knowledge regarding oral health and child health. 13,16 According to the study by Baykan et al, 16 the birth rank can affect the timing of the first deciduous tooth eruption, in contrast with the findings of the current study; this difference may result from population differences. There was no significant relationship between height and head circumference of infants, mother's age at birth and timing of the first deciduous tooth eruption in the current study, which was similar to the findings of Kutesa et al, 18 Vojdaniet al 20 On the other hand, Soliman et al, 17 Sujlana et al, 24 Oziegbo et al, 15 reported a positive relationship between the height of infants and the number of erupted teeth.…”
Section: [ E P U B a H E A D O F P R I N T ]contrasting
confidence: 83%
See 1 more Smart Citation
“…The role of SHS exposure after birth on ETE in children with birth weight <3000 g may have impact on many children. Completion of primary teeth is likely correlated with body height and body mass 29 . Therefore, morphological measures may be considered for confounding variables to estimate the association between SHS exposure and timing of tooth eruption of children.…”
Section: Discussionmentioning
confidence: 99%